2018
DOI: 10.1016/j.archger.2018.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Which obesity index is the best predictor for high cardiovascular disease risk in middle-aged and elderly population?

Abstract: VFR and WC were more strongly associated with high CVD risk than BMI among middle-aged and elderly persons in Taiwan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…There are a number of potential biological mechanisms to explain the relation between weight cycling and CVH metrics. Weight cycling may contribute to CVD risk by leading to preferential deposition of visceral fat (Chang et al, 2018) or perivascular adipose tissue, (Costa et al, 2018) which are more strongly associated with CVD risk. The biological mechanisms behind preferential fat deposition are not fully elucidated in humans, (Montani et al, 2006) but there are studies showing preferential changes in body composition after weight regain may be due to metabolic adaptation or slowing of resting metabolic rate.…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of potential biological mechanisms to explain the relation between weight cycling and CVH metrics. Weight cycling may contribute to CVD risk by leading to preferential deposition of visceral fat (Chang et al, 2018) or perivascular adipose tissue, (Costa et al, 2018) which are more strongly associated with CVD risk. The biological mechanisms behind preferential fat deposition are not fully elucidated in humans, (Montani et al, 2006) but there are studies showing preferential changes in body composition after weight regain may be due to metabolic adaptation or slowing of resting metabolic rate.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with obesity often suffer from lipid metabolism disorder[69], which leads to increase risk of CVD[70]. Exercise is especially known as an economic and effective approach to reduce fat accumulation, however, the results of this review comparisons of HIIT and MICT interventions revealed no significant differences in their effects on TG, TC, LDL, HDL.…”
Section: Discussionmentioning
confidence: 95%
“…Different obesity indices show different comorbidity risks. WC is more strongly associated with a high risk of cardiovascular disease (CVD) than BMI among middle-aged and elderly persons in Taiwan 4 5. BMI and WC are more positively correlated with insulin resistance than BF percentage 6…”
Section: Introductionmentioning
confidence: 99%